Implementasi Teknologi Motion Capture untuk Pengendalian Robot Lengan Menggunakan Sensor MPU-6050 dan Flex Sensor - Andri Suhartono (Institut Teknologi Adhi Tama Surabaya, 2023)
This research aims to evaluate the capability of motion capture technology in capturing the movement of the left human arm and applying it to an arm robot. In this research, three MPU-6050 sensors are used, which are a combination of 3D accelerometer and 3D gyroscope to obtain the position and orientation of the left human arm, as well as one flex sensor to obtain finger bend or hand grip data. In this research, the optimal processing and data transmission delay time is 75 ms. Test results show an average accuracy rate of 87% in controlling the robot for 30 seconds. Results obtained from the used sensors are stable when in motion, but there is a slight stability problem when in a stationary position. Overall, this research concludes that motion capture technology can be used to assist humans in controlling robot movement with precision and ease.